Ответы 1
Пошаговое объяснение:
4.
у=2/√(√(4х+13)) - 3/х²
F(x)=∫(2/(√(4x+13)) - 3/x²)dx=
=∫2/(√(4x+13))dx-∫3/x²dx=
=∫1/2√tdt-3∫1/x²dx=1/2∫1/√tdt-3•(-1/x)=
=1/2•2√t+3/x=1/2•2√(4x+13)+3/x=
=√(4x+13)+3/x +C, C∈R
A(-3;2)
F(-3)=2
√(4•(-3)+13)+3/(-3)+C=2
√1 -1+C=2
1-1+C=2
C=2
график, которой проходит через А(-3;2) имеет вид:
F(x)=√(4x+13) + 3/x +2
5.
{y-x=5 y=5+x
{√x+√y=5
√x+√(5+x)=5
(√x+√(5+x))²=5²
x+2√(x(5+x))+5+x=25
x+2√(5x+x²)+5+x=25
2x+2√(5x+x²)=25-5
2√(5x+x²)=20-2x
√(5x+x²)=10-x
(√(5x+x²))²=(10-x)²
5x+x²=100-20x+x²
5x=100-20x
25x=100
x=4
y=5+4
y=9
3х+4у=3•4+4•9=12+36=48
ответ: 48
ответы на свои вопросы
вопросы?